The effect of work environment, work stress, remuneration, work motivation on employee performance at Puskesmas X Padang City - Yanwar, Lila; Lupoto, Nur Indrwati (Institute of Computer Science (IOCS), 2025)
The problems that are the focus of this study are the problems of work environment variables, work stress and remuneration. The purpose of this study is to analyze the influence of work environment, work stress, remuneration, and work motivation on employee performance at Puskesmas X Padang City. This research method uses a quantitative approach, with a population of 96 employees of UPTD Puskesmas X Padang City. Sampling technique with a saturated sampling approach. The data analysis techniques used in this study were validity and reliability instrument tests, multiple linear regression tests, classical assumption tests and partial hypothesis tests tested with the t test while simultaneous hypotheses were tested with the F test. This can be seen from the significant value of t of 0.642 > 0.05. Work stress has a partially significant effect on employee performance at UPTD Puskesmas X Padang City, this can be seen from the significant value t of 0.000 < 0.05. Remuneration did not have a significant partial effect on employee performance at UPTD Puskesmas X Padang City, this can be seen from a significant value of t of 0.928 > 0.05, and work motivation did not have a significant effect on employee performance at Puskesmas X Padang City as seen from the t result of 0.878 > 0.005. Simultaneously the work environment, work stress, remuneration and work motivation have a significant influence on employee performance at UPTD Puskesmas X Padang City, this can be seen from the significant value of F of 0.005 < 0.05.